Atrial Fibrillation-Induced Cardiac Shock: First Manifestation of a Congenitally Corrected Transposition of the Great Arteries in a 45-Year-Old Man. (4th December 2012) - Graf, M.; Zaczkiewicz, M.; Torzewski, J.; Zimmermann, O.
Abstract : Background. The congenitally corrected transposition of the great arteries (L-TGA) is a very rare congenital heart defect, which often remains undetected for several decades of life. Case Presentation. We report on a 45-year-old man without prior history of heart disease, presenting with cardiac shock related to a first episode of tachycardic atrial fibrillation. The diagnostic work-up identified a L-TGA as the underlying cause for acute heart failure. Discussion. L-TGA is a very rare congenital heart defect, which is characterized by an atrioventricular as well as a ventriculoarterial discordance. By this means, the physiological sequence of pulmonary and systemic circulation is still maintained. On the basis of an ongoing strain of the right ventricle, which has to carry the burden of the systemic blood pressure, after more than four decades without symptoms, acute heart failure was triggered by a tachycardic atrial fibrillation.